Theoretical and methodical principles of air right of Ukraine are explored in the article - Шереметьєва, Є. Т. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
An author groundsan idea that the use of air space of Ukraine is straight related to providing of political,economic, social, ecological security of the state, welfare of population of a country.